2010
DOI: 10.1007/s11270-009-0302-7
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Potassium Ferrate (K2FeO4) for Simultaneous Removal of Heavy Metals and Natural Organic Matters from River Water

Abstract: This study has investigated how to simultaneously remove both heavy metals (Cu, Mn, and Zn) and natural organic matters (NOM; humic acid and fulvic acid) from river water using potassium ferrate (K 2 FeO 4 ), a multipurpose chemical acting as oxidant, disinfectant, and coagulant. In water sample including each 0.1 mM heavy metal, its removal efficiency ranged 28-99% for Cu, 22-73% for Mn, and 18-100% for Zn at the ferrate(VI) doses of 0.03-0.7 mM (as Fe). The removal efficiency of each heavy metal increased wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…The applicability of ferrate for removal of heavy metals (Lim et al 2010), cyanide (Lee et al 2009) , hydrogen sulfide (Sharma et al 1997), ammonia (Sharma et al 1998), arsenic (Lee et al 2003) or organic contaminants e.g. biphenol-A (Li et al 2008), carbohydrates (Sharma et al 2012), phenol and chlorophenols (Graham et al 2004), pharmaceutical residues (Sharma et al 2006), personal care products (Yang et al 2012) was demonstrated in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The applicability of ferrate for removal of heavy metals (Lim et al 2010), cyanide (Lee et al 2009) , hydrogen sulfide (Sharma et al 1997), ammonia (Sharma et al 1998), arsenic (Lee et al 2003) or organic contaminants e.g. biphenol-A (Li et al 2008), carbohydrates (Sharma et al 2012), phenol and chlorophenols (Graham et al 2004), pharmaceutical residues (Sharma et al 2006), personal care products (Yang et al 2012) was demonstrated in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods for the removal of heavy metal ions from water exist, such as chemical oxidation and reduction, membrane separation, liquid extraction, ion exchange, electrolytic treatment, electroprecipitation, coagulation, floatation, hydroxide and sulfide precipitation, ultrafiltration, and electrodialysis to name a few. However, these methods are often cost intensive, not suitable for drinking water treatment in rural areas or not applicable on a large scale.…”
Section: Introductionmentioning
confidence: 99%
“…Water pollution by heavy metals has become a public concern due to the development of high‐technology industries around the world . The long‐term intake of drinking water containing even low concentrations of heavy metals may cause fatal diseases by the accumulation of heavy metals in the internal organs of human body .…”
Section: Introductionmentioning
confidence: 99%